(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2024)
Osteoporosis is a progressive skeletal disorder characterized by decreased bone density and increased fragility, leading to a higher risk of fractures. This article explores the multifactorial causes of osteoporosis, examining genetic, hormonal, nutritional, and lifestyle factors. By analyzing existing literature and presenting original findings, this study aims to enhance the understanding of osteoporosis’ etiology and provide recommendations for prevention and management.